POP : Kultur und Kritik (transcript-Verlag, 2012)
The journal "Pop. Kultur und Kritik" features essayistic and scientificcontributions according to pop-cultural topics such as pop music, marketingand advertising, election campaigns and opinion polls, TV series andmagazines, fan conventions and internet blogs, fashion and everyday design,spectacles and events, DIY and cultural industries.